The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12051293
|View full text |Cite
|
Sign up to set email alerts
|

Common and Differential Traits of the Membrane Lipidome of Colon Cancer Cell Lines and Their Secreted Vesicles: Impact on Studies Using Cell Lines

Abstract: Colorectal cancer (CRC) is the fourth leading cause of cancer death in the world. Despite the screening programs, its incidence in the population below the 50s is increasing. Therefore, new stratification protocols based on multiparametric approaches are highly needed. In this scenario, the lipidome is emerging as a powerful tool to classify tumors, including CRC, wherein it has proven to be highly sensitive to cell malignization. Hence, the possibility to describe the lipidome at the level of lipid species ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…In addition, we observed a clear tendency in phosphatidylinositol (PI) decreasing in AD, Neo, and Her patients compared to healthy ones (14.9%, 10.5%, and 11.8%, respectively). These results are in line with the literature [48] and in agreement with our previous study in CRC cell lines [43].…”
Section: Isolated Ev Membrane Lipidome Shows Changes In Phosphatidylcholine Content In Compromised Patientssupporting
confidence: 94%
See 3 more Smart Citations
“…In addition, we observed a clear tendency in phosphatidylinositol (PI) decreasing in AD, Neo, and Her patients compared to healthy ones (14.9%, 10.5%, and 11.8%, respectively). These results are in line with the literature [48] and in agreement with our previous study in CRC cell lines [43].…”
Section: Isolated Ev Membrane Lipidome Shows Changes In Phosphatidylcholine Content In Compromised Patientssupporting
confidence: 94%
“…The analysis of commercial cell line-derived EVs showed that the lipid composition of these vesicles is very sensitive to their origin [ 43 ]. Thus, we sought to establish whether this discriminatory potential would persist in a more complex biological matrix and context: plasma and patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intensity of lipid species eliciting opposing trends in the experimental groups is exemplified by the ethyl ethers PC O-16:0/16:0 and PC O-16:0/18:1, which are expressed more strongly in malignant cells ( Figure S2A ), and by SM d18:1/16:0 and PE P-18:0/22:4, that were particularly abundant in melanocytes ( Figure S2B ). Figure S2 also provides clear examples of the heterogeneity in lipid expression across the cell lines analyzed, which were used to model a condition, as also seen for colon cancer cell lines [ 33 ].…”
Section: Resultsmentioning
confidence: 99%